Guidance and counseling on student congregational prayer discipline at madrasah aliyah islamic center bin baz yogyakarta - Suhartono; Havidz Cahya Pratama; Faiz Naufal; Agorovi Kuncoro (Yayasan Azhar Amanaa Yogyakarta, 2024)
Education aims to improve the quality of individuals to become pious individuals. Therefore, providing guidance to students must not only follow psychological and sociocultural principles, but must also pay attention to the fact that students are creatures created by Allah Ta'ala. Madrasah Aliyah Islamic Center Bin Baz Yogyakarta, as an Islamic boarding school-based educational institution, applies guidance and counseling to the discipline of congregational prayer. This research aims to evaluate the implementation of guidance and counseling at the institution. The method used is field research with a descriptive qualitative approach. Research subjects included school principals, student affairs, and guidance and counseling teachers. Data collection techniques consist of interviews, observation, and documentation, while data analysis is carried out through data reduction, data presentation, and drawing conclusions. The research results show that the implementation of counseling guidance begins with preventive efforts from the school, where the violation that occurs is being late in attending congregational prayers. Handling problematic students is carried out through dialogue directed at understanding religious values. The impact of counseling guidance can be seen in positive behavioral changes. Supporting factors in counseling guidance include opportunities for teachers for self-development and support provided by the school community. On the other hand, the challenges faced include a lack of understanding of the function of guidance and counseling among the school community and a lack of response to the problem of students who are late for congregational prayers.